Interorganizational Relationship Trends of Critical Access Hospitals. Issue 1 (15th July 2015) - Hearld, Larry R.; Carroll, Nathaniel W.
Abstract: Purpose: Examine the types of interorganizational relationships (IORs)—defined as formal linkages between 2 or more organizations to produce or coordinate some good or service—pursued by Critical Access Hospitals (CAHs), how these relationship patterns have changed over time, and how these relationships compare to non‐CAHs. Methods: We used univariate analyses to describe the prevalence of different types of formal horizontal (eg, system affiliation) and vertical (eg, physician organization, nursing home ownership) relationships for CAHs over time (2002‐2012) and chi‐square tests to compare the prevalence of these relationships to non‐CAHs. Findings: Contract management relationships were more prevalent among CAHs than other types of hospitals, and they declined over time for all types of hospitals. Network membership was more common among CAHs compared to rural, non‐CAHs. Tightly integrated relationships with physician organizations were more common among CAHs, relative to rural, non‐CAHs. Nursing home ownership was more prevalent among CAHs and rural, non‐CAHs relative to urban, non‐CAHs, but it declined over time for all hospital types. Conclusions: Our findings highlight a number of differences in the types of IORs pursued by CAHs relative to other types of hospitals and raise questions about the role of the Medicare Rural Hospital Flexibility Program in stimulating these differences. Our findings also suggest that even though the prevalence of hospitals engaging in any horizontal or vertical strategy was relatively stable, the fluctuations in the particular forms of these IORs were more dramatic.